PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUKASI MATEMATIS SISWA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Elis Hana Solihat; Eka Senjayawati; Nelly Fitriani; Tupa Minokti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to examine students' mathematical communication skills which included the material of Single Variable Linear Equation (PLSV) using a contextual approach. The type of research used is Classroom Action Research (CAR) with the subject of this research are 15 students of class VII-D in one of the public junior high schools in Cimahi city in the even semester of 2021-2022 which has a Minimum Completeness Criteria (KKM) value of 7.00. The data collection technique was carried out by conducting an initial test which was carried out before the action (pre-test), then doing the first cycle test and the second cycle which was carried out after giving the action (post-test), each cycle was carried out in 2 meetings. From each of the test questions, the results obtained that aspects of students' mathematical communication skills always increased from each cycle. Based on the data obtained in the initial pre-test there were 26.7%, the first cycle was 40%, there was an increase in the second cycle, namely 86.67% of students who completed. The conclusion of this study is that the mathematical communication skills of seventh grade junior high school students using a contextual approach can be improved.